Ideology and power relations in Ice-Cold documentary film: An Islamic communication perspective - Afifah, Afifah; Bakti, Andi Faisal; Hamad, Ibnu (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
The Ice-Cold documentary exposes Jessica Wongso's cyanide case, revealing legal irregularities and sparking critical discussion on media narratives. Prior studies highlight media’s influence on public opinion but overlook how ideology and power are embedded in narratives. This research fills that gap by analyzing their reflection in the documentary Ice Cold. This theory incorporates Islamic concepts such as istidl’af (Al-Qasas 5), musyawarah (Ali Imran 159), and khalaqah from the Prophet’s hadiths. Using qualitative discourse analysis, it explores the relationship between messages, ideology, and power. This study examines the relationship between ideology and power in the film Ice Cold, using Gill Branston and Roy Stafford’s theory and public perceptions post-release. Using media, communication, and da'wah approaches resulted in an analysis showing the power behind this case and how the social class between Jessica and Mirna can lead to public opinion. It is essential to acknowledge the possible non-neutrality of media and documentary films and the importance of critically assessing information obtained from the press. This research makes an academic contribution by expanding the study of ideology and power in the media by integrating Islamic concepts in discourse analysis. It also offers a new interdisciplinary perspective, linking communication theory, da'wah, and social representation to reveal power dynamics and ideological construction in documentary film narratives. ***** Film dokumenter Ice-Cold mengulas kasus sianida Jessica Wongso yang mengungkap kejanggalan hukum dan memicu dialog kritis mengenai narasi media. Studi sebelumnya membahas pengaruh media terhadap opini publik, tetapi mengabaikan bagaimana ideologi dan kekuasaan tertanam dalam narasi tersebut. Penelitian ini melengkapi gap tersebut dengan menganalisis refleksinya dalam dokumenter Ice-Cold. Teori ini mengintegrasikan konsep-konsep Islam seperti istidl’af (Al-Qasas ayat 5), musyawarah (Ali Imran ayat 159), dan khalaqah dari hadits Nabi. Dengan menggunakan metode kualitatif dan analisis wacana, teori ini mengeskplorasi hubungan antara pesan film, ideologi dan kekuasaan. Penelitian ini mengkaji hubungan antara ideologi dan kekuasaan dalam film ice Ice-Cold dengan menggunakan teori Gill Branston dan Roy Stafford serta persepsi publik setelah film tersebut dirilis. Dengan menggunakan pendekatan media, komunikasi, dan dakwah menghasilkan sebuah analisis yang menunjukkan kekuatan di balik kasus ini serta bagaimana kelas sosial antara Jessica dan Mirna dapat menggiring opini publik. Penting untuk mengakui kemungkinan ketidaknetralan media dan film dokumenter dan pentingnya menilai secara kritis informasi yang diperoleh dari pers. Penelitian ini memberikan kontribusi akademik dengan memperluas kajian ideologi dan kekuasaan dalam media melalui integrasi konsep-konsep Islam dalam analisis wacana. Juga menawarkan perspektif baru yang bersifat interdisipliner, yang menghubungkan teori komunikasi, dakwah, dan representasi sosial, untuk mengungkap dinamika kekuasaan dan konstruksi ideologi dalam narasi film dokumenter.